2020
DOI: 10.3389/fpls.2020.589005
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the miR164c-Guided Gene/Protein Interaction Network Controlling Seed Vigor in Rice

Abstract: MicroRNAs (miRNAs) play important roles in various aspects of plant physiology and metabolism. The expression level of miR164c is negatively correlated with seed vigor in rice ( Oryza sativa L.); however, the mechanism of seed vigor regulation by miR164c remains unknown. Anti-aging capacity is an important indicator of seed vigor. Here, we report an miR164c-guided gene/protein interaction network that regulates the anti-aging ability of rice seeds. Seeds of the wild-type (WT) rice cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Seed germination rate is an important indicator of seed vigor. The results of RT-qPCR analysis and germination test indicated that after 8 days of artificial aging, the expression level of miR164c and germination rates of WT, MIM164c and OE164c seeds differed significantly, consistent with previous studies [ 10 , 11 ]. Regardless of aging, OE164c seeds showed the highest miR164c expression level and the lowest germination rate, whereas MIM164c seeds displayed the lowest miR164c expression level and the highest germination rate (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Seed germination rate is an important indicator of seed vigor. The results of RT-qPCR analysis and germination test indicated that after 8 days of artificial aging, the expression level of miR164c and germination rates of WT, MIM164c and OE164c seeds differed significantly, consistent with previous studies [ 10 , 11 ]. Regardless of aging, OE164c seeds showed the highest miR164c expression level and the lowest germination rate, whereas MIM164c seeds displayed the lowest miR164c expression level and the highest germination rate (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In addition to the previously reported miR164c-guided RPS27AA -related pathway [ 11 ], the network contained at least other seven KEGG pathways: ‘ascorbate and aldarate metabolism’ ‘plant hormone signal transduction’ ‘galactose metabolism’ ‘nucleotide excision repair’ ‘TCA cycle’ ‘oxidiative phosphorylation’ and ‘flavonoid biosynthesis’ (Fig. 4 ), of which the RPS27AA -related pathway and three KEGG pathways that directly interact with the target genes of miR164s were simplified as Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, the peptides were combined into 6 fractions and dried by a vacuum-type centrifuge. LC-MS/MS Analysis and Database Search were conducted according to the previously published method ( Huang et al, 2020 ). Briefly, we subjected the peptides to an NSI source, followed by MS/MS in Q ExactiveTM (Thermo Fisher Scientific, Waltham, MA, United States) coupled with UPLC online.…”
Section: Methodsmentioning
confidence: 99%